DETERMINAN STRES, KECEMASAN DAN DEPRESI PADA PASIEN PENYAKIT JANTUNG KORONER: Determinants Of Stress, Anxiety, And Depression Among Patients With Coronary Heart Disease - Tika Dwi Tama; Mazidah Imanuna; Hartati Eko Wadhani (Journal of Community Mental Health and Public Policy, 2020)
Stress, anxiety, and depression are known to worsen the quality of life of patiens with coronary heart disease (CHD). However, the detection of mental health conditions has not been carried out in an integrated way in the management of CHD patients. The purpose of this study was to assess the determinants of stress, anxiety, and depression in CHD patients at RSUD Dr. Saiful Anwar. This cross-sectional study was carried out from December 2019 to January 2020 in the cardiac polyclinic of RSUD Dr. Saiful Anwar, Malang. CHD patients who underwent outpatient care at the cardiac clinic in 2019 were the population in this study. A total of 90 CHD patients were selected purposively to be the study sample. Logistic regression was used to determine the predictors of stress, anxiety, and depression among CHD patients. The study found that as many as 17.8% of CHD patients experienced mild to very severe stress, 47.8% experienced mild to very severe anxiety, and 66.7% experienced mild to very severe depression. Sex, age, heart failure status, emotional support, instrumental support, and information support were not predictors of stress, anxiety, or depression (p-value> 0.05). Monitoring mental health conditions and providing psychoeducation should be done during the outpatient care. It is expected to ensure the mental health of CHD patients in good condition.